The Importance of Parents Role in Developing Early Childhood Emotional Intelligence - Huda, Azkia Nabila; Wita Arawia (Socrates: Journal of Education, Philosophy and Psychology, 2025)
The role of parents is very crucial in developing emotional intelligence in early childhood, especially in the golden period of child development (0-6 years). Emotional intelligence includes the ability to recognize, manage emotions, empathize, and build healthy social relationships. This intelligence does not develop naturally, but requires consistent parenting, guidance and education. Parents, especially mothers, play a role as the main educators in shaping children's personality, behavior and social-emotional competencies through positive interactions and providing good role models. . Support for children's creativity, independence and communication is the main factor in this process. Children with good emotional intelligence will grow into confident individuals, able to resolve conflicts, and have strong social skills. This research emphasizes the importance of parental strategies in building emotional intelligence in early childhood to support their short-term and long-term success.